2015
DOI: 10.1016/j.jmbbm.2015.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of inter-lamellar behaviour of the intervertebral disc annulus

Abstract: The inter-lamellar connectivity of the annulus fibrosus in the intervertebral disc has been shown to affect the prediction of the overall disc behaviour in computational models. Using a combined experimental and computational approach, the inter-lamellar mechanical behaviour of the disc annulus was investigated under conditions of radial loading.Twenty-seven specimens of anterior annulus fibrosus were dissected from 12 discs taken from four frozen ovine thoracolumbar spines. Specimens were grouped depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…This is due to two phenomena: the lamellae getting closer or further away from each other due to the changes in their fibre alignment, and the fibre bundles being pulled apart or closer to each other. Previous work by Mengoni et al [34] reported an inter-lamella stiffness higher than intra-lamella. Those authors, however, applied a very specific loading to a thin radial slice of annulus whereas in this case the composite-like structure of the annulus was not compromised.…”
Section: Discussionmentioning
confidence: 80%
“…This is due to two phenomena: the lamellae getting closer or further away from each other due to the changes in their fibre alignment, and the fibre bundles being pulled apart or closer to each other. Previous work by Mengoni et al [34] reported an inter-lamella stiffness higher than intra-lamella. Those authors, however, applied a very specific loading to a thin radial slice of annulus whereas in this case the composite-like structure of the annulus was not compromised.…”
Section: Discussionmentioning
confidence: 80%
“…Some of the experiments that have been used that indirectly assessed the ILM are radial tensile tests of intact tissue and with enzymatic digestion or cross‐linking, shear testing, NP pressurization of the intact disc, and peel testing . One recent study, however, has directly assessed ILM mechanical properties . In this study, the stiffness of the ILM under radial loading was consistently higher than the corresponding lamellar values, and was measured to be greater at the outer (43–75% higher) relative to the inner AF.…”
Section: Inter‐lamellar Matrix Micromechanical Propertiesmentioning
confidence: 76%
“…Complexity of the elastic fibers in the ILM including their thickness and coil‐like structures with high degree of elastin–fibrillin co‐localization have been suggested to play a mechanical role; however, their impact on AF mechanical properties and integrity is unknown. Therefore, using lamellae that were concentric and physically isolated when developing computational models of the AF, may not be an appropriate representation …”
Section: Inter‐lamellar Matrix Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…The initial stiffness values of the lamellar and inter-lamellar springs, kl,0 and kitalicil,0, were derived from an elastic model (Mengoni et al, 2015). The damaged springs were modelled in line with the continuum damage mechanics theory (Lemaitre and Desmorat, 2005).…”
Section: Methodsmentioning
confidence: 99%